Notching on Cancer’s Door: Notch Signaling in Brain Tumors - Teodorczyk, Marcin; Schmidt, Mirko H. H. (Frontiers in Oncology, 2015)
Notch receptors play an essential role in the regulation of central cellular processes during embryonic and postnatal development. The mammalian genome encodes for four Notch paralogs (Notch 1-4), which are activated by three Delta-like (Dll1/3/4) and two Serrate-like (Jagged1/2) ligands. Further, non-canonical Notch ligands such as EGFL7 have been identified and serve mostly as antagonists of Notch signaling. The Notch pathway prevents neuronal differentiation in the central nervous system by driving neural stem cell maintenance and commitment of neural progenitor cells into the glial lineage. Notch is therefore often implicated in the development of brain tumors, as tumor cells share various characteristics with neural stem and progenitor cells. Notch receptors are overexpressed in gliomas and their oncogenicity has been confirmed by gain- and loss-of-function studies in vitro and in vivo. To this end, special attention is paid to the impact of Notch signaling on stem-like brain tumor-propagating cells as these cells contribute to growth, survival, invasion and recurrence of brain tumors. Based on the outcome of ongoing studies in vivo, Notch-directed therapies such as γ secretase inhibitors and blocking antibodies have entered and completed various clinical trials. This review summarizes the current knowledge on Notch signaling in brain tumor formation and therapy.